2004
DOI: 10.1007/s10310-003-0069-4
|View full text |Cite
|
Sign up to set email alerts
|

Response of gas exchange rates inAbies firmaseedlings to various additional stresses under chronic acid fog stress

Abstract: In order to clarify the chronic influence of acid fog on the gas exchange rates of momi fir (Abies firma Sieb. et Zucc.) trees, we exposed them to simulated acid fog (pH 3) for 3 years. The composition of the acid fog was similar to that observed in a region where momi fir trees have been declining, and it contained organic acids. We then treated the firs with various additional stresses, such as drought, low temperature, fine root cutting, ozone exposure, soil acidification, nitrogen load, and rhizosphere alu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Soil pH (H 2 O) values after treatment are shown in a previous report (Yoshida et al 2004). A proton loading of 6 kg H ϩ /ha per year for 17 months did not cause any distinct decrease in soil pH, although we confirmed that this proton loading level could decrease the soil pH to 5.8 in the absence of seedlings.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Soil pH (H 2 O) values after treatment are shown in a previous report (Yoshida et al 2004). A proton loading of 6 kg H ϩ /ha per year for 17 months did not cause any distinct decrease in soil pH, although we confirmed that this proton loading level could decrease the soil pH to 5.8 in the absence of seedlings.…”
Section: Resultssupporting
confidence: 82%
“…We analyzed momi fir (Abies firma) seedlings treated with acid fog and soil acidification or nitrogen loading as shown in a previous study (Yoshida et al 2004), which gives a full description of the plant materials used, growth conditions of momi fir seedlings, and methods of acid fog exposure and proton or nitrogen loading.…”
Section: Methodsmentioning
confidence: 99%
“…We found no distinct complex effect of acid fog with Al on nutrient status. Integration of the results of this study with those of the previous report, in which these stress treatments had no effect on transpiration rate or photosynthesis rate of momi fir seedlings (Yoshida et al 2004), shows that the alterations in nutrient status are not sufficiently serious to induce the decline of photosynthesis rate of momi fir seedlings. Eamus D, Fowler D (1990) Effects Acid fog n.s.…”
Section: Resultsmentioning
confidence: 59%
“…Half of the seedlings were exposed to simulated acid fog of pH 3.0 twice weekly from mid-July 1999, while the remaining seedlings were not exposed. The details on growth conditions and acid fog exposure methods are described elsewhere (Yoshida et al 2004).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation